2019
DOI: 10.4236/ajps.2019.1012162
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Ions and Organic Solutes Accumulation in Amaranth (<i>Amaranthus cruentus</i> L.) Salinity Resistance

Abstract: Salinity is one of the major environmental constraints limiting agricultural productivity in the world. The effects of salt stress on growth, ions and organic solutes accumulation were investigated in two amaranth (Amaranthus cruentus) cultivars: Rouge (salt-resistant) and Locale (salt-sensitive). Young plants of these cultivars were exposed, in hydroponic system, to three concentrations of NaCl: 0, 30 and 90 mM. Growth parameters, ions, free proline and soluble sugars concentrations were determined after 2 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 55 publications
2
8
0
1
Order By: Relevance
“…For these reasons, our research was focused on Na + . Results of this study showed that salt stress induced a significant increase in Na + content in both leaves and roots corroborating several previous reports on vegetable species [34,25]. In some genotypes of sweet basil, similar result was reported [21,19].…”
Section: Effect Of Salt Stress On Plant Ion Contentsupporting
confidence: 92%
“…For these reasons, our research was focused on Na + . Results of this study showed that salt stress induced a significant increase in Na + content in both leaves and roots corroborating several previous reports on vegetable species [34,25]. In some genotypes of sweet basil, similar result was reported [21,19].…”
Section: Effect Of Salt Stress On Plant Ion Contentsupporting
confidence: 92%
“…Salinity caused an increase in Na content and a decrease in K content in the leaves as well as in the roots in tomato cultivar Padma plants evaluated in this study. This response of plant ion nutrition to salt stress in a common behavior as reported by several authors [40,41,42,43,28], suggesting that the NaCl detrimental effect on plant growth was due mainly to both Na toxicity and K deficiency. As revealed by our results, the exogenous application of both calcium forms improved plant mineral nutrition by reducing Na accumulation and enhancing K accumulation in both leaves and roots.…”
Section: Implication Of Ions and Organic Solutes In The Ameliorative Effect Of Calcium On Plant Growth Under Salt Stresssupporting
confidence: 75%
“…As revealed by our results, the exogenous application of both calcium forms improved plant mineral nutrition by reducing Na accumulation and enhancing K accumulation in both leaves and roots. Reducing Na accumulation and enhancing K accumulation mainly in leaves is one of the common plant strategies to tolerate NaCl salt stress as reported in several glycophyte species [44,45,46,43,28]. In okra (Abelmoschus esculentus), Habib et al [42] reported that the foliar application of both pure glycine betaine and sugarbeet extract reduced the adverse effects of salt stress on plant growth, yield and leaf K content.…”
Section: Implication Of Ions and Organic Solutes In The Ameliorative Effect Of Calcium On Plant Growth Under Salt Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Par ailleurs, plusieurs travaux ont révélé que la réduction de la croissance des plantes d'amarante sous l'effet de la salinité est principalement la conséquence de l'accumulation d'ions devenant toxiques (Na + et Cl -) pour les activités métaboliques de la plante (Omami, 2005 ;Odjegba et Chukwunwike., 2012). En effet, ces ions peuvent perturber la capacité de la plante à contrôler l'accumulation d'autres ions importants (Wouyou et al, 2019). Parmi ces ions, l'ion sodium (Na + ) occupe une place de choix.…”
Section: Introductionunclassified